2018
DOI: 10.1038/s41598-018-35079-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering a large animal model of human hypophosphatasia in sheep

Abstract: The availability of tools to accurately replicate the clinical phenotype of rare human diseases is a key step toward improved understanding of disease progression and the development of more effective therapeutics. We successfully generated the first large animal model of a rare human bone disease, hypophosphatasia (HPP) using CRISPR/Cas9 to introduce a single point mutation in the tissue nonspecific alkaline phosphatase (TNSALP) gene (ALPL) (1077 C > G) in sheep. HPP is a rare inherited disorder of mineral me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…If an incompatible PAM or target site sequence is introduced into the genome via the knock-in, the sgRNA-Cas9 complex can no longer bind to the target site, and no further edits can be made. The use of ssODN to induce knock-in or to improve knockout efficiency has been reported recently in ruminant species (sheep: [15,16]; goats: [17]; cows [27]).…”
Section: The Repair Templatementioning
confidence: 99%
See 3 more Smart Citations
“…If an incompatible PAM or target site sequence is introduced into the genome via the knock-in, the sgRNA-Cas9 complex can no longer bind to the target site, and no further edits can be made. The use of ssODN to induce knock-in or to improve knockout efficiency has been reported recently in ruminant species (sheep: [15,16]; goats: [17]; cows [27]).…”
Section: The Repair Templatementioning
confidence: 99%
“…When SCNT is mastered by the laboratory, the low efficient rate will be compensated with most of the healthy born animals carrying the desired mutation. Genome editing mediated by SCNT is applied by some laboratories in some kind of projects (e.g., multiplex editing), but the high efficiency of CRISPR after direct microinjection into zygotes has allowed an easier approach (sheep: [6,7,15,16]; goats: [9,17]; pigs: [11,13]). All together, these reports showed that with CRISPR it is possible to perform direct microinjection into the zygote of different species, with minimum effects on developmental competence and pregnancy rates, high newborn survival rate, and high editing rate with acceptable homozygous proportion.…”
Section: Embryo Manipulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data provide another proof-of-principle for using HDR to precisely modify the sheep genome 28 . This has been shown to be useful for producing human disease models in areas where sheep more physiologically relevant 28 . The HDR approach was convenient as the appearance of a known allele simplifies the screening of strains.…”
Section: Discussionmentioning
confidence: 77%